Exome sequencing reveals pathogenic mutations in 91 strains of mice with Mendelian disorders - Fairfield, Heather; Srivastava, Anuj; Ananda, Guruprasad; Liu, Rangjiao; Kircher, Martin; Lakshminarayana, Anuradha; Harris, Belinda S.; Karst, Son Yong; Dionne, Louise A.; Kane, Coleen C.; Curtain, Michelle; Berry, Melissa L.; et al.

(untitled) (Genome Research, 2015)
Spontaneously arising mouse mutations have served as the foundation for understanding gene function for more than 100 years. We have used exome sequencing in an effort to identify the causative mutations for 172 distinct, spontaneously arising mouse models of Mendelian disorders, including a broad range of clinically relevant phenotypes. To analyze the resulting data, we developed an analytics pipeline that is optimized for mouse exome data and a variation database that allows for reproducible, user-defined data mining as well as nomination of mutation candidates through knowledge-based integration of sample and variant data. Using these new tools, putative pathogenic mutations were identified for 91 (53%) of the strains in our study. Despite the increased power offered by potentially unlimited pedigrees and controlled breeding, about half of our exome cases remained unsolved. Using a combination of manual analyses of exome alignments and whole-genome sequencing, we provide evidence that a large fraction of unsolved exome cases have underlying structural mutations. This result directly informs efforts to investigate the similar proportion of apparently Mendelian human phenotypes that are recalcitrant to exome sequencing.